PREFERENSI MASYARAKAT TERHADAP PEMILIHAN JENIS POHON DALAM PENGELOLAAN HUTAN BERBASIS MASYARAKAT : Studi Kasus di Desa Paramasan Bawah, Kabupaten Banjar, Kalimantan Selatan - Titien Maryati (Lambung Mangkurat University-Indonesia, 2011)
The purpose of this study was to identify the types of trees that were developed and planted a tree pattern, perception and motivation of households to plant trees and to know the status of land use for agriculture and gardening in the context of food security.Research conducted in the Village Paramasan Bawah, ParamasanDistrict, Banjar Regency. The research was divided into 3 phases of the study was the preparation phase, implementation phase of the research and report preparation. The research was designed using a case study approach as an empirical inquiry that investigates a phenomenon within the context of real life today (Yin, 2002). In general, case studies provide wide access and opportunities for researchers to examine in depth, detailed study, intensive and comprehensive than the social unit. Case studies can provide important information about the relationship between variables and processes that require explanation and a broader understanding. In addition to presenting case study data and findings are very useful as a basis for building the background to the problem of planning a larger study and in-depth in order to develop knowledge (Yin, 1997; Aziz, 2003). Species of trees, which was developed by community of Paramasan Bawah rubber, candles, Cempedak, Rambutan, durian, nangka, jengkol, petai, pampakin, kapul, Tan, cinnamon, mango, teak, mahogany, sungkai, hambawang, lahung, areca nut, hampalam and kangkala.perception of the community to create a picture by entering the type of tree crops based on the acceptance for long-term economic value, because the wood production plants are usually quite long, so strategy by mixing with cropsPREFERENSI MASYARAKAT TERHADAP PEMILIHAN JENIS POHON DALAM PENGELOLAAN HUTAN BERBASIS MASYARAKAT : Studi Kasus di Desa Paramasan Bawah, Kabupaten Banjar, Kalimantan Selatan